Physical education, exercise and sports science in a changing society - Freeman, William H. 1943- (Jones & Bartlett Learning, 2015)
Written for the introductory or foundational course, the eighth edition provides a modern, comprehensive, and balanced entry to the fields of physical education, exercise science, and sport science. This revision outlines the origin and development of these disciplines and looks forward to their application of the latest data and technologies. It identifies current conflicts and includes discussion on the changing focuses of the field and the broader realms it encompasses